2019
DOI: 10.1002/adma.201903778
|View full text |Cite
|
Sign up to set email alerts
|

Do Zinc Dendrites Exist in Neutral Zinc Batteries: A Developed Electrohealing Strategy to In Situ Rescue In‐Service Batteries

Abstract: The dendritic issue in aqueous zinc‐ion batteries (ZBs) using neutral/mild electrolytes has remained an intensive controversy for a long time: some researchers assert that dendrites severely exist while others claim great cycling stability without any protection. This issue is clarified by investigating charge/discharge‐condition‐dependent formation of Zn dendrites. Lifespan degradation (120 to 1.2 h) and voltage hysteresis deterioration (134 to 380 mV) are observed with increased current densities due to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
447
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 565 publications
(475 citation statements)
references
References 57 publications
8
447
0
Order By: Relevance
“…The nonuniform and dented surface of the bare Zn anode can be observed from the cross‐sectional SEM images (Figure S8a,b, Supporting Information). After 100 cycles, it is noteworthy that the dendrite formation can be obviously observed on the bare Zn anode at high current density even in the mild electrolyte, which is consistent with the previous reported results 39. Considering the large polarizations and the short cycle life of the bare Zn anode in Figure 4, it can be speculated that these serious cracks can be the indication of the severe Zn corrosion caused by the occurrence of HER and shape change due to the uncontrollable nucleation.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The nonuniform and dented surface of the bare Zn anode can be observed from the cross‐sectional SEM images (Figure S8a,b, Supporting Information). After 100 cycles, it is noteworthy that the dendrite formation can be obviously observed on the bare Zn anode at high current density even in the mild electrolyte, which is consistent with the previous reported results 39. Considering the large polarizations and the short cycle life of the bare Zn anode in Figure 4, it can be speculated that these serious cracks can be the indication of the severe Zn corrosion caused by the occurrence of HER and shape change due to the uncontrollable nucleation.…”
Section: Resultssupporting
confidence: 92%
“…Surface coating layer on anode acts as a protective layer to decrease the contact area between electrode and electrolyte, suppressing the HER and Zn corrosion during cycling. Zhi's group developed a porous nano‐CaCO 3 coating to achieve uniform Zn stripping/plating, and it is also found that the Zn dendrites formation would be facilitated with increased current densities, where the electrohealing methodology can be expected to eliminate already‐formed dendrites 38,39. The electrolyte optimization positively influences the performance of Zn anode by forming a smooth absorbed layer or decreasing the active of H 2 O in the electrolyte, leading to the dendrite‐free anode and guaranteeing the long cycle life of battery.…”
Section: Introductionmentioning
confidence: 99%
“…Structure optimization strategies such as Zn/CNT, [ 3 ] Zn@ZnO‐3D, [ 4 ] Cu foam@Zn [ 5 ] were introduced to accelerate uniform Zn 2+ deposition and alleviate the dendrite issue in neutral electrolyte. [ 6 ] Ion‐conductive polymer electrolytes can effectively restrain the growth of Zn dendrites and alleviate the dissolution of active materials owing to their limited water content. [ 7 ] A kind of “water‐in‐salt” ultrahigh concentration electrolyte of 1 m Zn(TFSI) 2 + 20 m LiTFSI was designed to reduce the H 2 O molecules that surround Zn 2+ , wherefore it could effectively suppress the Zn dendrites and side reactions, [ 8 ] which was also achieved by using ZnCl 2 ·2.33H 2 O, [ 9 ] 30 m ZnCl 2 , [ 10 ] Zn(CF 3 SO 3 ) 2 , [ 11 ] “water‐in‐deep eutectic solvent” of urea electrolyte.…”
Section: Introductionmentioning
confidence: 99%
“…At a rate of 0.1 A g −1 , a reversible discharge capacity of 73 mAh g −1 could be maintained after 100 cycles. More importantly, at the relatively high rate of 0.2 A g −1 , although the capacity is rapidly decreased at the initial stage (probably due to the lattice distortion and the information of zinc dendrites), it is stabilized at around 40 mAh g −1 from the 50th to 1000th cycles with almost no capacity fading (Figure g and Figure S1). Such stable performance is superior to that of most reported aqueous zinc‐ion pouch cells…”
Section: Resultsmentioning
confidence: 99%